Pola Kerjasama Guru dan Orang Tua dalam Meningkatkan Mutu Pendidikan di MIN 2 Kota Palembang - Mgs Nazarudin (Pusat Penelitian dan Penerbitan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Raden Fatah Palembang, 2018)
Focus of the discussion in this study was the collaboration of parents and MIN 2 teachers in Palembang City in improving the quality of education. The problems that were deliberately raised in this study were: What efforts were made by MIN 2 Palembang in building cooperation between parents and teachers? What is the form of collaboration between student’s parents and teachers in improving the quality of education in MIN 2 Palembang? In line with the formulation of the problem, the purpose of this study is to find out: (1) School efforts to establish cooperation with student’s parents; (2) Form of collaboration between school and student’s parents. This research is a field research using a qualitative descriptive approach. The subject of this study was school MIN 2 Palembang City. Data collection techniques used were interviews and documentation. The researcher is the main instrument in conducting research assisted by interview sheets and documentation guidelines. Sources of data or key information are three people (Head of MIN 2 Palembang City and 2 teachers). The collected data was then analyzed using qualitative descriptive. The results of the study show that: (1) School efforts to establish cooperation with parents of students are by creating a comfortable school climate, making initial communication with parents, and providing opportunities for parents to be involved in school activities; (2) Forms of cooperation carried out include: parenting, communication, volunteers, parental involvement in children's learning at home, and collaboration with community groups.